Co-evolvierende + co-respondierende Systeme = co-operierendes System - Aurada, Klaus D. (ERDKUNDE, 2003)
The geosystem approach in geography can be traced back to impulses and developments effective towards the end of the 19 th century. The spatially differentiated reflection of long-term and short-term processes of the past and their structural expressions which serve as the carriers of present and future processes characterize geosystems as conservative cellular systems. The heterogeneous structure of the geosystem reflects its heterochrone development: physiogenic self-organization and self-regulation are characteristical for evolving and responding geosystems (example: Baltic Sea area), anthropogenic organization and regulation are characteristical for convergent or divergent colonization and implementation of geosystems; physiogen-anthropogenic systems represent co-evolving and co-responding systems and finally a co-operating system. Example: dam building and controlling in Northern, Central and Southern Europe.